Measurement of User Satisfaction Level in the Bina Darma Information Systems Study Program Portal Using End User Computing Satisfaction Method - Nurul Adha Oktarini Saputri; Alvin Alvin (Journal of Information System and Informatics, 2020)
Information systems study program portal is a website developed by Bina Darma University that aims to be a media for promotion and academic information system study programs. User satisfaction is the most important thing to be a benchmark for developers of information systems study program portals to improve the quality of their websites so that users are more satisfied and do a lot of searching activities, especially academic activity searches. But so far the information systems study program portal developer does not yet know the shortcomings of the information system study program portal, so analysis is needed to measure the level of user satisfaction. In an effort to achieve User Satisfaction with the portal of the bina darma information system study program which has the si.binadarma.ac.id domain, researchers used the end user satisfaction method (EUCS). The EUCS instrument includes five components: content, accuracy, format, ease of use, and schedule. The data in this study were collected with a questionnaire instrument that was distributed to students from the information systems study program. Furthermore, the data obtained were processed using SPSS software version 24. The sampling technique used in this study was simple random sampling. The results of this study are expected to be a reference to improve the quality of information systems study program portals. Keywords: website, user satisfaction, EUCS